1973
DOI: 10.1007/bf02531810
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of lowered cholesterol oxidation in guinea pigs with latent vitamin C deficiency

Abstract: Fifty‐two male guinea pigs fed on a scorbutigenic diet were divided into a control group (10 mg ascorbicacid per animal per day) and a group with latent vitamin C deficiency (2 weeks on the scorbutigenic diet only, followed by a maintaining dose of 0.5 mg ascorbic acid per animal per day). After 13 weeks, 26‐14C‐cholesterol was administered intraperitoneally to all the animals, in which the14C excretion in the expired CO2 and the urine and cholesterol specific activity in the blood serum and liver were then st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The role of vitamin C in bile acid biogenesis has mainly been analysed in guinea pigs [3-9]. Cholesterol is converted to bile acids in the liver, and the rate limiting process depends on vitamin C concentration in the hepatocytes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The role of vitamin C in bile acid biogenesis has mainly been analysed in guinea pigs [3-9]. Cholesterol is converted to bile acids in the liver, and the rate limiting process depends on vitamin C concentration in the hepatocytes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the accumulation of TC in serum of ODS-od/od rats fed with a commercial diet was not so much higher than the results of experiments using guinea pigs chronically fed with a vitamin C-deficient diet (15,16), ODS-od/od rats fed with a cholesterol supplied diet resulted in a significant increase of TC in serum and liver. Our result is the same as that of Horio et al using ODS rats fed with a diet supplied 0.5% cholesterol and 0 .25% cholic acid (17).…”
Section: Discussionmentioning
confidence: 64%
“…From the above results, exogenous loading of an inadequately large dose of lipid, we also can assume that ODS-od/od rats have a disorder in the excretion pathway of choles terol. Ginter (16) reported that vitamin C is a cofactor of a key enzyme, 7a hydroxylase, in this pathway to bile acid (18). There have been only a few reports proving this hypothesis because the method of measurement of this enzyme is not easy.…”
Section: Discussionmentioning
confidence: 99%
“…The role of AA in lipid metabolism has been studied extensively in guinea pigs as, like humans, they are incapable of synthesizing AA. Long term hypovitaminosis C resulted in the accumulation of cholesterol in blood serum and/or a number of tissues, including the liver and the thoracic aorta [9], possibly due to a decreased rate of cholesterol catabolism [ 10,11 ] . In genetically modified rats unable to synthesize AA, AA deficiency resulted in elevated serum and liver concentrations of cholesterol regardless of whether rats were fed a normal or cholesterol-containing diet [12] .…”
Section: Effect Of Aa On Lipid Metabolismmentioning
confidence: 99%
“…AA may influence lipid metabolism in different ways. In guinea pigs, the catabolism of cholesterol to bile acids is hindered by low AA levels [11,[54][55][56][57]. A significant linear correlation has been observed between the rate of cholesterol conversion to bile acids and the AA concentration in the liver of guinea pigs [ii, 55].…”
Section: Effect Of Aa On Lipid Metabolismmentioning
confidence: 99%